Program Eco Town sebagai Langkah untuk Melindungi Ekosistem Sungai di Perkotaan - Maysanda Rahmanisa Zahra; Reza Yudha Sakti; Dinita Ardiyanti (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2024)
The implementation of environmental law influenced the success of the Eco Town program in maintaining the sustainability of river ecosystems by providing a strong foundation for preserving the environment. The implementation of strict regulations related to environmental protection and river management is key in ensuring that development within Eco Town does not damage the river ecosystem. In several case studies such as the Ciliwung River and the Brantas River, the implementation of environmental law has recorded significant improvements in the sustainability of river ecosystems. The main challenges faced in implementing environmental laws to support Eco Town programs are resource limitations, especially in terms of funds, technology, and natural resources. These limitations may hinder the effectiveness of the program and affect the ability to address environmental problems such as industrial or domestic waste management, and maintain ecological balance. To overcome these challenges, concrete measures such as improved accessibility and technology transfer, sustainable management of natural resources, and investment in environmental infrastructure are needed. By ensuring a solid environmental law implementation and paying attention to these limitations, the Eco Town program can run more effectively and efficiently in maintaining the sustainability of the river ecosystem and realizing a vision of sustainable development.